68+9=t/9

Simple and best practice solution for 68+9=t/9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 68+9=t/9 equation:



68+9=t/9
We move all terms to the left:
68+9-(t/9)=0
We add all the numbers together, and all the variables
-(+t/9)+68+9=0
We add all the numbers together, and all the variables
-(+t/9)+77=0
We get rid of parentheses
-t/9+77=0
We multiply all the terms by the denominator
-t+77*9=0
We add all the numbers together, and all the variables
-1t+693=0
We move all terms containing t to the left, all other terms to the right
-t=-693
t=-693/-1
t=+693

See similar equations:

| 2(x-1)-3=13 | | (1+6x)=3x+5 | | (3x-9)+(6x-5)=85 | | X^2+12=x-3 | | -11-11x=68 | | 2+43x+420=0. | | 13e=169 | | 14=7(x+2) | | 31=22-3/10b | | 4a-11=2(a+6) | | X^2-2x-0.6=0 | | X/6x30=180 | | 7(x+2)+4x=6(2x-4) | | (1/2y-1)/2=y/12 | | 8(x+7)=4(x+3) | | (3x^2+2)^2=13 | | (1/2y-1/2)=y/12 | | (1+r)^5=1.33 | | 1/2y-1/2y=y/12 | | 〖(1+r)〗^5=1.33 | | 13-x^2=-77 | | 1/2y-12/2y=y/12 | | -x^2+13=-77 | | (4x-1)=65 | | 20+10t=5t | | 33+21=s+14 | | 4+4+3+3+x+x=24 | | 180=3/8x+50 | | 121-x²=0 | | 3x-6=2x-7. | | ∣6x∣−8=22 | | (5/2n)=98-n |

Equations solver categories